Implementasi Akuntansi Manajemen Berbasis Digital sebagai Alat Pengukuran Kinerja Sumber Daya Manusia pada UMKM di Kabupaten Buleleng - Luh Seriadnyani; Komang Krisna Heryanda (KRISNA: Kumpulan Riset Akuntansi, 2026)
Abstract This study aims to analyze the implementation of digital-based management accounting as a tool for measuring human resource (HR) performance in Micro, Small, and Medium Enterprises (MSMEs) in Buleleng Regency. Digital transformation has significantly influenced financial recording systems and management control practices, including within small and medium-sized enterprises. However, the utilization of digital accounting systems as instruments for HR performance evaluation remains underexplored, particularly in regional MSME contexts. This research adopts a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation from selected MSMEs that have implemented digital accounting systems. Data analysis employed the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing, with validity ensured through source and method triangulation. The findings indicate that the implementation of digital-based management accounting enhances financial transparency, facilitates employee productivity monitoring, and supports performance evaluation based on quantitative indicators such as sales target achievement and labor cost efficiency. Nevertheless, challenges include limited digital literacy and resistance to changes in work systems. This study contributes theoretically by enriching the discourse on digital management accounting within MSME contexts and practically by offering recommendations to optimize digital systems for improving HR performance. Keywords: Digital Management Accounting, Human Resource Performance, MSMEs, Digital Transformation, Case Study